2015
DOI: 10.1242/dev.126953
|View full text |Cite
|
Sign up to set email alerts
|

The NIMA-like kinase Nek2 is a key switch balancing cilia biogenesis and resorption in the development of left-right asymmetry

Abstract: Vertebrate left-right (LR) asymmetry originates at a transient left-right organizer (LRO), a ciliated structure where cilia play a crucial role in breaking symmetry. However, much remains unknown about the choreography of cilia biogenesis and resorption at this organ. We recently identified a mutation affecting NEK2, a member of the NIMAlike serine-threonine kinase family, in a patient with congenital heart disease associated with abnormal LR development. Here, we report how Nek2 acts through cilia to influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 67 publications
(103 reference statements)
0
28
0
Order By: Relevance
“…The authors observed that the cilia and motile cilia counts were in nek2 morphants and hNEK2 overexpressors. Additionally, NEK2 overexpression promotes increased cilia resorption by phosphorylation of Nup98 [24].…”
Section: Nek2mentioning
confidence: 99%
“…The authors observed that the cilia and motile cilia counts were in nek2 morphants and hNEK2 overexpressors. Additionally, NEK2 overexpression promotes increased cilia resorption by phosphorylation of Nup98 [24].…”
Section: Nek2mentioning
confidence: 99%
“…The cilium's permeability barrier is also characterized by the presence of Nups, including FG-containing Nups [22,31], and has thus been termed the ciliary pore complex (CPC, Figure 2). To study the function of FG-containing Nups in gated entry, Takao et al developed a “pore clogging assay” by rapid and specific crosslinking of the central channel nucleoporin Nup62 [32**].…”
Section: Generating a Unique Luminal Protein Compositionmentioning
confidence: 99%
“…Nek2 controls cilia disassembly; depletion of Nek2 causes an increase in the number of ciliated cells [ 8 ]. Nek2 has been linked directly to disruption of left-right asymmetry, a biological consequence of cilia dysfunction [ 10 ]. Nek2 also regulates intraflagellar transport (IFT) through phosphorylation of the kinesin KIF24 to stimulate cilia depolymerization [ 11 ].…”
Section: Introductionmentioning
confidence: 99%